Frequency and pattern reconfigurable dipole-Yagi antenna - Ezla Najwa, Ahyat; Muhammad Ramlee, Kamarudin, Assoc. Prof. Dr.; Tharek, Abd. Rahman, Prof. Dr.; Mohd Faizal, Jamlos, Dr.; Mohamad Rijal, Hamid, Dr.; Mohd. Haizal, Jamaluddin, Dr.; Nur Hidayah, Ramli (Wiley Periodicals, Inc., 2013)
Link to publisher's homepage at http://onlinelibrary.wiley.com/